Budaya Organisasi dalam Membangun Literasi Karyawan PT Bagindo Kayu Putih Selatan - Harneet Kaur; Davis Roganda Parlindungan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The existence of a culture of reading books / literacy in the PT Bagindo Kayu Putih Selatan company is a phenomenon that is still rarely found among the public, especially in companies. Due to the lack of sensitivity to issues and understanding of the employees, the founders of the company created an organizational culture by establishing a Book Reading Club for their employees, every day they read one book and then discussed it together. Organizational Culture according to Robbins 2003: 305 (in Sulaksono 2015)) explains that organizational culture is a system of shared meanings held by members that distinguishes an organization from other organizations. This research was investigated with a post-positivistic paradigm with a qualitative approach that aims to examine the phenomenon in depth, the method used is a case study. Based on the results of interviews and observations made, it can be concluded that in addition to building literacy and adding insight, the purpose of the founders of the company is to train employees in communicating and arguing so that they can act optimally in the digital world to their audiences.